Efficacy and crop tolerance of Stamina (pyraclostrobin) and Flite (triticonazole) seed treatment formulations against Fusarium, Pythium and Rhizoctonia soilborne diseases of maize - Aveling, Terry A.S. (University of Pretoria, 2013)
Dissertation (MSc (Agric))--University of Pretoria, 2013.